The quest for a globally comprehensible Russula language (2019)
Since 2007, the quality of Russula descriptions has improved and the use of molecular support for species delimitation and the number of published new species has increased. However, the description style is not consistent and has regional or author-specific patterns. Most recent publications still favour descriptions of spores compared to hymenium and pileipellis elements, and usually only the spore size is provided with statistical support. This study proposes standards for descriptions of the microscopic structure of Russula species (Russulaceae, Agaricomycetes). We present the description template, the template measurements table, the specific terminology and the essential chemical reagents. The proposed standards were tested by mycologists from 11 countries who met at the Russula Microscopy Workshop in Slovakia. Descriptions of 26 species from 9 countries and four continents were prepared, among them R. amarissima, R. castanopsidis, R. seperina and R. subtilis are re-described and 15 species are introduced as new: R. abietiphila, R. amerorecondita, R. aurantioflava, R. echidna, R. flavobrunnescens, R. fluvialis, R. fortunae, R. garyensis, R. gemmata, R. laevis, R. madrensis, R. olivaceohimalayensis, R. purpureogracilis, R. sancti-pauli and R. wielangtae. Seven descriptions for candidate new species are provided without a formal name assignment. Pairwise comparison of species described in this study with available similar descriptions of related species suggests that microscopic characters from all parts of the basidiomata can be equally important for species recognition and they deserve the same treatment including number of measurements and statistics. The majority of recent studies does not recognise differences between the pileus margin and centre, but more than one-third of the species described in this study show distinct differences between the pileus areas, emphasizing the importance to specify the origin of pileipellis observations. This study proved that there is frequently insufficient difference in the ITS barcode between closely related species and that it is necessary to use more genetic markers combined with ecological and geographical data. © 2019, School of Science.